Green olives fermentation profile by using Lactobacillus pentosus DSM 16366 as a starter culture - Pintado, Cristina Miguel (2006)
Modern large-scale production of fermented foods i focused on the use of defined stain starter systems to ensure consistency and quality in the final product. In Spanish-styles green olives process, initial conditions are usually somewhat restrictivefor the growth of desirable microorganisms.